2010
DOI: 10.1627/jpi.53.292
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodesulfurization Activity of Co–Mo/Al<sub>2</sub>O<sub>3</sub> Catalysts Prepared with Citric Acid: Post-treatment of Calcined Catalysts with High Mo Loading

Abstract: Co _ Mo/Al2O3 catalysts with high loading of Mo (20 wt% Mo) were prepared by the addition of citric acid (CA) using a simultaneous impregnation method or a post-treatment method. The catalyst activity was investigated for the hydrodesulfurization (HDS) of dibenzothiophene. TEM, Co K-edge XANES, NO adsorption capacity, and surface area measurements were conducted to characterize the catalysts. The catalysts were also investigated by the chemical vapor deposition technique using Co(CO)3NO to prepare Co/MoS2 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Transition metals have been widely studied due to their numerous applications, such as catalysts in a wide variety of industrial processes involving reduction atmosphere and the activation or conversion of hydrocarbons [1][2][3]. The catalytic performance is determined by the chemical structure of the catalyst and its properties [4].…”
Section: Introductionmentioning
confidence: 99%
“…Transition metals have been widely studied due to their numerous applications, such as catalysts in a wide variety of industrial processes involving reduction atmosphere and the activation or conversion of hydrocarbons [1][2][3]. The catalytic performance is determined by the chemical structure of the catalyst and its properties [4].…”
Section: Introductionmentioning
confidence: 99%
“…175 The posttreatment was also very efficient to increase the activity for the HDS of DBT at 1.48 MPa. 176 Furthermore, it is suggested that the post-treatment method is applicable to the regeneration of deactivated HDS catalysts. 176 It was revealed with XAFS, Raman, and UVvis spectroscopic studies that CoCA and MoCA surface citrate complexes are formed by the post-treatment with citric acid at the expense of CoMoO 4 and polymolybdates.…”
mentioning
confidence: 99%
“…176 Furthermore, it is suggested that the post-treatment method is applicable to the regeneration of deactivated HDS catalysts. 176 It was revealed with XAFS, Raman, and UVvis spectroscopic studies that CoCA and MoCA surface citrate complexes are formed by the post-treatment with citric acid at the expense of CoMoO 4 and polymolybdates. 174,175 In situ XAFS was used to disclose the sulfidation behaviors of Co and Mo in CoMo/B-Al 2 O 3 prepared by use of the post-treatment with citric acid for further characterizations of favorite nature of the catalyst preparation.…”
mentioning
confidence: 99%